Impact of heating conditions on the carbon and oxygen isotope composition of calcined bone. (January 2016) - Snoeck, Christophe; Schulting, Rick J.; Lee-Thorp, Julia A.; Lebon, Matthieu; Zazzo, Antoine
Abstract: Only the inorganic fraction of bone survives the high temperatures reached during cremation, so that it remains the sole material available for isotopic analyses. In order to assess the amount of information that can be extracted from such material, we measured carbon and oxygen isotope ratios in the remaining carbonate fraction of experimentally heated modern bone, and cremated bone from several archaeological sites. The results show that the isotope composition of cremated bone is strongly altered, but some information can nevertheless be extracted. First, we find very little evidence of post-burial alterations on the isotope composition of calcined bone. More importantly, it appears possible to obtain information about the way bodies were burned (with or without fuel, oxygen availability) giving the opportunity to improve our knowledge regarding funerary practices in places and times where cremation was practiced. Highlights: Experimentally burned and archaeological cremated bone were analysed by IRMS. Carbon and oxygen isotopes of bioapatite carbonate are heavily altered by cremation. These are mostly influenced by the fuel used in the pyre. It appears possible to identify bones heated under different conditions. The results confirm the high resistance to post-burial alterations of calcined bone.